BUDAYA HIDUP BERSIH DAN SEHAT DI SEKOLAH DASAR UNTUK MEMBANGUN GENERSI MUDA YANG BERKARAKTER - Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2016)
To developing character of young people can apply a few indicators of clean and healthy behaviours in school, that: 1) washing hands with water and shop, 2) taking the food of healthy, 3) use latrines clean and healthy, 4) regular exercise and measurable, 5) not smoking, 6) throw garbage into the dumpster disaggregated, 7) eradicating wiggler, 8) weigh and measure height, 9) maintaining the hair so clean and neat, 10) clean and neatly dressed, 11) maintaining the nail to keep it short and clean. Each indicator of healthy behaviour and clean there is values characters such as of discipline, healthy life, love and care for the environment.